Correlation of Nitrite Oxide with Severity and Survival Rate of Sepsis Patients - Sotianingsih Sotianingsih; Budi Mulyono; Andaru Dahesihdewi; Samsirun Halim; Ahmad Syauqi (Indonesian Association of Clinical Pathologist and Medical laboratory, 2021)
The objective of this research was to determine the correlation between Nitric Oxide (NO) levels with the severity of sepsis, to describe the kinetics of NO levels, and to evaluate it in predicting mortality. This research was a longitudinal cohort observational analytical study. The variables were serum NO levels and SOFA scores, which were serially evaluated. The correlation test and difference test were used for statistical analysis. The survivor and the non-survivor group consisted of 14 (41.18%) and 20 (58.82%) patients, respectively. There was a correlation between serum NO levels and the SOFA score at the 24-hour observation (r=0.403; p=0.041). Non-parametric Mann-Whitney test showed that there was no kinetics of NO th levels at 0, 24, 72, and 144-hour observation (p-values =0.897 and 0.703, respectively). NO levels > 111,16 Î¼mol/L at the 24 hour could predict the risk of death with hazard ratio 4.7 compared to NO levels < 111,16 Î¼mol/L. The survival rate of patients with serum NO levels <111,16 Î¼mol/L and > 111,16 Î¼mol/L was 83.3% and 37.5%, respectively. There was a correlation between serum NO levels and SOFA scores at the 24-hour observation. However, there was no kinetics of NO levels at serial evaluations. Nitric oxide levels with a cut-off of 111,16 Î¼mol/L at 24 hours could predict the survival of septic patients. Utilization of serum NO level at 24 hour can be used to evaluate the severity of septic patients and aggressive management if there is an increase in serum NO levels > 111,16 Î¼mol/L at 24 hours.